Inhibiting Factors in the Adoption of Corporate Entrepreneurship at a State-Owned Agency in South Africa - Nthangeni, Aluwani; Lebambo, Marcia (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: Corporate Entrepreneurship (CE) has been used to develop new ideas and opportunities within established organisations, resulting in improved profitability, service delivery, and competitive advantages. This study explored the factors inhibiting CE adoption at the state agency in South Africa. It aims to expand on dimensions and provide practical interventions for creating a conducive environment for CE within a state-owned agency. Design/methodology/approach: The study used a qualitative single-case study design. It employed semi-structured interviews with nine top management and Human Resources (HR) practitioners through Microsoft Teams. The study used inductive coding to analyse interview data using ATLAS.ti 23. Findings: Challenges emerged as a theme for this study with four sub-themes: rewards, financial constraints, lack of knowledge of the CE process and low staff morale. The study revealed that these challenges inhibit the adoption of CE. In contrast, addressing these challenges can transform them into enabling factors that create a conducive environment for adopting CE. The study underscored the significance of optimising resource utilisation to promote CE, enhancing CE knowledge, and evaluating employee satisfaction. Research limitations/implications: The study was limited to top management experts and HR practitioners, excluding other employees' participation. Practical implications: Emphasises the need for practical interventions such as brainstorming, team coaching, credible e-learning platforms, and employee satisfaction surveys when implementing CE. Originality/value: There are limited studies on the inhibitors of CE in South Africa's state-owned agencies. Paper type: Research paper.